HAK-HAK ANAK DIBAWAH UMUR SELAKU TERSANGKA PENYALAHGUNAAN NARKOTIKA PADA PROSES PENYIDIKAN DI DIREKTORAT RESERSE NARKOBA POLDA METRO JAYA - Dio Tafta Adji; Ahmad Sobari (JOURNAL OF LAW AND NATION, 2024)
The regulation of narcotics crimes committed by minors is basically not specifically regulated in Law Number 35 of 2009 concerning Narcotics, but the application of sanctions is always linked to Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. If the understanding of the SPPA Law and other regulations relating to Juvenile Criminal Justice is incorrect, then the application in carrying out actions related to the investigation is also incorrect, and this is very detrimental to children. Based on this, the researcher formulates the problem, namely: 1). How the law regulates narcotics and the perpetrators of criminal acts of narcotics abuse by minors; 2). How are the rights of minors as suspects of narcotics abuse in the investigation process?; 3). How are efforts to fulfill the rights of minors as suspects of narcotics abuse in the future? By using normative juridical research, it is concluded that Narcotics Crimes are regulated in Law Number 35 of 2009 concerning Narcotics. For cases of criminal offenses of narcotics abuse by minors are different from adult suspects. The investigation process in the juvenile criminal justice system prioritizes the best interests of the child and seeks a family atmosphere where one of the forms is a diversion effort and the investigator is obliged to ask for consideration or advice from the community counselor. The fulfillment of children's rights involving drug abuse has been regulated in the Child Criminal Justice System Law and the Child Protection Law. Efforts to fulfill the rights of minors as suspects of drug abuse in the future are regulated by investigators regarding Restorative Justice and Diversion. Here it is necessary to have an understanding of PPA investigators of the rights of children in the judicial process including filling the legal vacuum and the fulfillment of institutional facilities regulated in UUSPA.